Not Too Warm, Not Too Cold: Thermal Treatments to Slightly Warmer or Colder Conditions from Mother’s Origin Can Enhance Performance of Montane Butterfly Larvae - Konstantina Zografou; George C. Adamidis; Brent J. Sewall; Andrea Grill (Biology, 2022)
Climate change alters organismal performance via shifts in temperature. However, we know little about the relative fitness impacts of climate variability and how cold-adapted ectotherms mediate these effects. Here, we advance the field of climate change biology by directly testing for species performance, considering the effects of different thermal environments at the first developmental stage of larvae. We conducted our experiments in climatic chambers (2019–2020) using five cold-adapted butterflies of the genus Erebia (Erebia aethiops, Erebia cassioides, Erebia manto, Erebia tyndarus, Erebia nivalis). Larvae were reared indoors and were treated with higher and lower temperatures than those of their mothers’ origins. Overall, we found evidence of better performance at warmer temperatures and a decreased performance at lower temperatures, and larvae were able to tolerate small temperature changes from mother’s origin. Warmer conditions, however, were unfavorable for E. nivalis, indicative of its limited elevational range and its poor ability to mediate a variety of thermal conditions. Further, larvae generally performed poorly where there was a large difference in thermal regimen from that of their maternal origin. Future efforts should include additional life history stages and focus on a more mechanistic understanding of species thermal tolerance. Such studies could increase the realism of predicted responses to climate change and could account for asynchronous changes in species development, which will alter community composition and ecosystem functioning.